13 | Improving Herpes Zoster vaccination coverage: evidence and strategies for the de-seasonalization of vaccine delivery in the Local Health Authority of Catania - F. Fiorito; G. Giorgianni; A. Aleo; M. Fichera; R. Vinci; R. Furnari; M. Palella; A. Mistretta (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2026)
Background. Herpes Zoster (HZ) is a disease with a significant public health impact, particularly among older adults and vulnerable populations. Deseasonalizing vaccine delivery could improve the quality of vaccination services while also enhancing equity of access. In the Local Health Authority (ASP) of Catania, 3,035 first doses and 2,531 second doses (5,566 total doses) were administered in 2024; in 2025, the corresponding figures were 3,041 and 2,521 doses (5,562 total doses). The resident population aged 65 years and older amounts to 240,101 individuals (ISTAT 2025), indicating that vaccination coverage remains suboptimal. Materials and Methods. A descriptive observational study was conducted using data from the Regional Unified Vaccination Registry of the ASP of Catania for the years 2024–2025. HZ vaccine administrations were analyzed according to demographic, clinical, and temporal variables. Results. In 2025, among individuals receiving the first dose, 53.8% were female and the median age was 69 years. The most frequently recorded comorbidities were cardiovascular diseases, diabetes mellitus, solid tumors, and chronic respiratory diseases. Monthly analysis of first-dose administrations showed variability in vaccine uptake during both years, with peaks in November–December and the lowest numbers during the summer months, particularly in August. However, during the period affected by the influenza vaccination campaign (October–January), a reduction in HZ vaccinations was observed in 2025 compared with 2024. Conversely, from February to June, an increase in vaccine administrations emerged, suggesting the early effects of a deseasonalization process. Conclusions. The data reveal initial signs of deseasonalization in HZ vaccine delivery. Nevertheless, the concentration of vaccinations during October, November, and December still suggests the influence of the concurrent influenza vaccination campaign. Deseasonalization strategies, combined with continuous information campaigns and the involvement of General Practitioners (GPs), are essential to improve vaccination coverage, accessibility, and the overall effectiveness of the vaccination system.